Frederick R. Weisman Collection. (Seoul : The National Museum of Modern Art, 1986)
Alberola, Jean-Michel ; Albers, Josef ; Amat, Frederic ; A-One (Anthony Clark) ; Arakawa ; Ard, Saradell ; Arman ; Arnoldi, Charles ; Artschwager, Richard ; Bachman, James ; Barsch, Wolf Erich ; Basquiat, Jean-Michel ; Baziotes, William ; Bell, Larry ; Biederman, Charles ; Chia, Sandro ; Christo ; Closky ; Gilbert and George ; Irwin, Robert ; Phillips, Jay ; etc.
Frederick R. Weisman Collection, The National Museum of Modern Art, Seoul, August 25 - October 10, 1986
boek